Attenuation of High Glucose-Induced Damage in RPE Cells through p38 MAPK Signaling Pathway Inhibition - Maugeri, Grazia; Bucolo, Claudio; Drago, Filippo; Rossi, Settimio; Di Rosa, Michelino; Imbesi, Rosa; D’Agata, Velia; Giunta, Salvatore (Frontiers in Pharmacology, 2021)
This study aimed to investigate the high glucose damage on human retinal pigment epithelial (RPE) cells, the role of p38 MAPK signaling pathway and how dimethyl fumarate (DMF) can regulate that. We performed in vitro studies on ARPE-19 cells exposed to normal (NG) and high glucose (HG) conditions, to assess the effects of DMF on cell viability, apoptosis, and expression of inflammatory and angiogenic biomarkers such as COX-2, iNOS, IL-1β and VEGF. Our data have demonstrated that DMF treatment attenuated HG-induced apoptosis, as confirmed by reduction of BAX/Bcl-2 ratio. Furthermore, in RPE cells exposed to HG we observed a significant increase of iNOS, COX-2 and IL-1β expression, that was reverted by DMF treatment. Moreover, DMF reduced the VEGF levels elicited by HG, inhibiting p38 MAPK signaling pathway. The present study demonstrated that DMF provides a remarkable protection against high glucose-induced damage in RPE cells through p38 MAPK inhibition and the subsequent down-regulation of VEGF levels, suggesting that DMF is a small molecule that represents a good candidate for diabetic retinopathy treatment and warrants further in vivo and clinical evaluation